Comparative morphology of the female genital ducts of seven eubrachyuran crabs (Saint Laurent, 1980). (18th January 2016) - de Souza, Leonardo Peres; Ogawa, Cynthia Yuri; Silva, José Roberto Feitosa; Camargo‐Mathias, Maria Izabel
Abstract: Three brachyuran groups can be defined based on genital orifices' location: coxae – Podotremata, coxal (males) or sternal (females) – Heterotremata and sternal – Thoracotremata. Aiming to compare Heterotremata (three species) and Thoracotremata (four species), we provide a detailed morphological description of the genital ducts. To do so, 50 females were collected and dissected, and macroscopic and histological description of their reproductive system is presented. In all of the specimens, the system is bilaterally sy, consisting a pair of ovaries and of genital ducts. Also, genital ducts have four components: oviduct, seminal receptacle, vagina and gonopore. Ovaries may be connected to seminal receptacle through dorsal or ventral region. In the Heterotremata studied, both types are observed, while it is only ventral in Thoracotremata. Seminal receptacle has two regions in all species: ventral – simple columnar secretory epithelium, apical region covered with cuticle, and middorsal – epithelium could be columnar secretory or stratified. Vagina is concave in all analysed Thoracotremata and simple in Heterotremata. An operculum was observed in all the Thoracotremata. Observed morphological patterns are consistent throughout Thoracotremata, while varying in Heterotremata, that is the way ovary and receptacle are connected and the kind of epithelia that forms the receptacle.